The role of the newspaper and of sudents’ memories in the construction of the identity of a different school: A Torre (Foro de Educacion, 2018)
This article was written within the INOVAR project, whose purpose is to understand the historical course and to characterize the pedagogical model of a set of «different» schools that were established in Portugal during the twentieth century. The school which is studied in this text – A Torre – is one of these schools. It is a cooperative school that is located in Lisbon, which was founded by Ana Maria Vieira de Almeida in 1970 (that is, in the final years of the Portuguese authoritarian regime) and which is still open nowadays. The peculiar and creative way in which the founder and the educators of A Torre appropriated several elements of the progressive pedagogical tradition gives this school a unique culture and identity. Its educational project has in Freinet’s pedagogy one of its most solid pillars. This has clear implications in some of the school’s educational practices, amongst which we may emphasise the holding of assemblies, the use of the wall newspaper or the production of a school newspaper with students’ contributions. The cooperative pedagogy and the education for democracy and for participation are central elements in the educational project of A Torre. This article aims to discuss the role of the newspaper as an experience of students’ self-government. Moreover, and in particular, it aims to reflect on the memories of former students about their experiences of living in a different school, which were collected in a set of testimonies that were published in the commemorative newspaper of the institution’s 40 years. We hope to discuss, in broad terms, the role of memories in the construction of the institutional identity.